La disciplina y efectividad de las bancadas de oposición en el Parlamento en los casos de interpelaciones durante los gobiernos de Toledo, García y Humala (2001-2013) - Vela, Estelí; Ruiz, Gabriela; García, Sebastián; Roca, Pablo (Pontificia Universidad Católica del Perú, 2014)
This article discusses the use of the mechanism of parliamentary control of interpellation to ministers in the Peruvian case, with the objective of stablish which factors determine the effectives of opposition groups to approve the motions of interpellations they present during the post- Fujimori goverrnments of Alejandro Toledo, Alan García and Ollanta Humala (2001-2013). Taking into account the size, discipline and the number of motions presented, this research argues that the most effective parliamentary groups have high levels of discipline and present a reasonable number of motions, in relation to their capacity to approve them. The levels of discipline and effectiveness of each parliamentary group were calculate through the recompilation ofdata from 85 motions and 36 debates about the admission of the process.

Este artículo aborda el uso del mecanismo de control político parlamentario de interpelación a ministros en el caso peruano, con el objetivo de identificar cuáles son los factores que influencian en la efectividad de las bancadas de oposición para aprobar las mociones de interpe- lación durante los gobiernos post-Fujimori de Alejandro Toledo, Alan García y Ollanta Humala (2001-2013). Tomando en cuenta el tamaño, la disciplina y el número de mociones presentadas por cada bancada parlamentaria, se concluye que las bancadas más efectivas son aquellas que tienen un alto nivel de disciplina y que presentan un número de mociones razonable, de acuerdo a su capacidad para aprobarlos. Para hallar los niveles de disciplina del voto y efectividad se recopiló los datos de 85 mociones de interpelaciones y de 36 votaciones sobre su admisión.
The discipline and effectiveness of the opposition groups in Parliament in the cases of interpellations during the governments of Toledo, Humala and García (2001-2013)
Keywords: Politics; Mechanisms Of Parliamentary Control; Interpellation; Opposition Groups; Parliamentary Discipline; Legislative Voting; Executive Control And Legislative Success; Mecanismos de Control Político; Interpelación; Bancadas de Oposición; Disciplina Parlamentaria; Control del Ejecutivo y Efectividad Legislativa; https://purl.org/pe-repo/ocde/ford#5.06.00